2013
DOI: 10.1016/j.ijgo.2013.03.015
|View full text |Cite
|
Sign up to set email alerts
|

Association between socioeconomic status and ectopic pregnancy rate in the Republic of Korea

Abstract: Older age and low socioeconomic status were risk factors for ectopic pregnancy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
25
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 27 publications
(30 citation statements)
references
References 6 publications
5
25
0
Order By: Relevance
“…T he incidence of diagnosis of ectopic pregnancy (EP), defined as the implantation and development of the embryo outside the uterine cavity (1), has increased during the mid-twentieth century, plateauing at approximately 2 per 100 pregnancies in Europe (2), North America (3), and Asia (4), and representing the fourth most frequent cause of maternal death in the United Kingdom (5). The rising incidence is mainly associated with an increased prevalence of pelvic inflammatory and sexually transmitted diseases, utilization of in vitro fertilization technologies, increased tubal sterilization practice and subsequent reversal attempts, as well as the use of levonorgestrel as an emergency contraceptive method (6)(7)(8)(9)(10)(11).…”
mentioning
confidence: 99%
“…T he incidence of diagnosis of ectopic pregnancy (EP), defined as the implantation and development of the embryo outside the uterine cavity (1), has increased during the mid-twentieth century, plateauing at approximately 2 per 100 pregnancies in Europe (2), North America (3), and Asia (4), and representing the fourth most frequent cause of maternal death in the United Kingdom (5). The rising incidence is mainly associated with an increased prevalence of pelvic inflammatory and sexually transmitted diseases, utilization of in vitro fertilization technologies, increased tubal sterilization practice and subsequent reversal attempts, as well as the use of levonorgestrel as an emergency contraceptive method (6)(7)(8)(9)(10)(11).…”
mentioning
confidence: 99%
“…Interestingly, the SDP had a similar success rate and a lower adverse effect rate compared with the non‐SDPs in a subgroup analysis of tubal pregnancies only. Considering that tubal pregnancies account for 90% of all ectopic pregnancies, this finding is clinically important . In other words, the SDP may be superior to non‐SDPs in the medical treatment of tubal pregnancy.…”
Section: Discussionmentioning
confidence: 99%
“…Ectopic pregnancy is a condition in which the embryo implants outside of the intrauterine cavity . The incidence of ectopic pregnancy is approximately 1–2% of all pregnancies, and ectopic pregnancy accounts for 3–4% of pregnancy‐related deaths . Various noninvasive methods (transvaginal sonography; measurement of β‐human chorionic gonadotropin [β‐hCG] and serum progesterone levels) are used to diagnose ectopic pregnancy …”
Section: Introductionmentioning
confidence: 99%
“…This is supported by Yuk JS and co-workers study which found low socioeconomic status as a risk factor for ectopic pregnancy. 15 The reason may be because lower socioeconomic status is associated with poor hygienic conditions, which predisposes to pelvic inflammatory disease and ectopic pregnancy.…”
Section: -13mentioning
confidence: 99%